Soups, shakes and other slimming strategies: GLP-1 agonists vs. NHS type 2 diabetes path to remission programme in the battle against T2DM and weight management - Divanshi Trivedi; Ruth Crowley (Clinical Medicine)
Introduction: Excess body weight increases the risk of cardiometabolic complications, morbidity, and mortality in patients with type 2 diabetes mellitus (T2DM).1 Effective management should prioritise medications that promote weight loss or remain weight-neutral to improve insulin sensitivity and blood glucose control. Glucagon-like peptide 1 (GLP-1) agonists are well established in T2DM treatment. They mimic the incretin hormone GLP-1, enhancing insulin secretion, suppressing glucagon release and slowing gastric emptying. These actions lower HbA1c, improve insulin sensitivity and promote weight loss. Beyond pharmacological options, dietary interventions have been studied for weight loss and glycaemic control. NHS England, in collaboration with Diabetes UK, launched the Type 2 Diabetes Path to Remission Programme (T2DR) for individuals diagnosed with T2DM for less than 6 years and above a specific healthy weight. The programme replaces all anti-diabetic medications with a 12-week meal replacement diet, leading to an average weight loss of 16 kg, with one-third of participants achieving remission.2 This project compared the effectiveness of GLP-1 agonists and the T2DR programme in improving weight loss and HbA1c levels to determine the superior approach for T2DM management. Methods and materials: This was a retrospective analysis of 5,650 patients from a single GP surgery using SNOMED-coded data to identify patients started on GLP-1 agonists or T2DR. Patients on GLP-1 agonists via private prescription were excluded. This analysis was conducted by filtering patients using keywords, such as ‘T2DM’, ‘T2DR’, and drug names, including ‘semaglutide’, ‘liraglutide’ and ‘dulaglutide’. Results and Discussion: Within a single GP surgery, n=7 patients with T2DM and raised body mass index (BMI; >30 kg/m2) began treatment with a GLP-1 agonist in 2024 (86% started on semaglutide). Comparatively, n=15 patients, were deemed eligible and enrolled on the T2DR programme. Analysis showed that patients who started treatment with a GLP-1 agonist had a maximal weight reduction of 17% and maximal weight gain of 10% across an average of 123 days. By contrast, patients completing the 12-week T2DR course experienced a maximal weight reduction of 21%. No patient gained weight while on this programme. On review of improvements in HbA1c, the GLP-1 agonist caused a maximal reduction of 11 mmol/L in HbA1c. The total meal replacement programme achieved a drop in HbA1c of 59 mmol/L. Conclusion: GLP-1 agonists have gained significant media attention as an effective weight loss treatment. Currently, National Institute of Health and Care Excellence (NICE) guidelines recommend their use in T2DM when triple therapy with metformin and two other oral drugs is ineffective or not tolerated, particularly for individuals with a BMI ≥35 kg/m2 with obesity-related complications or those with a lower BMI where insulin therapy would significantly impact daily life.3 Ongoing shortages of GLP-1 agonists have limited their access for many patients. This study suggests that the T2DR programme may offer a more accessible and sustainable alternative, delivering faster and more substantial weight loss and HbA1c control. Further research is needed to evaluate the long-term impact of T2DR, including weight maintenance and HbA1c changes as patients transition back to a regular diet, as well as a comparison with long-term GLP-1 agonist therapy.